CLINICAL ACTIVITY OF PHYSICAL REHABILITATION EXPERTS IN UKRAINE: PROBLEMS AND PROSPECTS - Bismak, Olena V. (Educological discourse, 2016)
The article is devoted to topical issues of professional training of specialists in physical rehabilitation, including the organization of clinical activity in rehabilitation centers. In the article the analysis of different aspects of the clinical activity of specialists in physical rehabilitation, the basic components (patient examination, diagnosis, determination of locomotors capacities, forecasts and a plan of measures, providing consultancy, implementation of intervention programs, providing recommendations for the independent operation) are presented. Attention is given to working out of a rehabilitation diagnosis in clinical practice, the use of the International Classification of Functioning, Disability and Health in the clinical activities of physical rehabilitation specialists. The main parts of the rehabilitation potential of patients are described. The role of clinical practice in training students for future physical therapists in clinical activities are shown.